PENGARUH DISIPLIN KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PEKERJAAN UMUM KOTA BALIKPAPAN - Manalu, Rivaldo; Hadiyatno, Didik; Arrywibowo, Imam (Jurnal Edueco, 2026)
This study aims to determine the effect of work discipline, motivation, and work environment on job satisfaction of employees of the Balikpapan City Public Works Department. This type of research uses a quantitative approach with a survey method. The study population was 103 employees and a sample of 97 employees consisting of civil servants and PPPK, which were determined using a purposive sampling technique. Data collection was carried out through a questionnaire with a Likert scale and data analysis using the Partial Least Square (PLS) method with the help of SmartPLS software. The results of this study indicate that work discipline and motivation have a positive and significant effect on employee performance, while the work environment has a negative and insignificant effect on employee job satisfaction.